Consumer choice under certainty and uncertainty in applied econometrics - Bernt P. Stigum (Economics and Econometrics Research Institute (EERI), 2021)
The paper lists salient characteristics of the certainty theory of consumer choice and discusses the import of prominent empirical analyses of the theory. All of them reject the theory's empirical relevance which suggests that the theory is unfit to analyze consumer choice in an uncertain world. The paper presents an extension of the certainty theory to a theory about consumer choice under uncertainty in which consumer behavior has interesting new properties. I conclude with an empirical test of the empirical relevance of an uncertainty version of Stone's Linear Expenditure System. In the given empirical context Stone's System is empirically relevant.
Keywords: A12; B23; B41; C01; C18; C30; C45; C51; C52; D12; D41; D59; 330; Utility function; linear expenditure system; almost ideal demand system; income and substitution effects; expectations' effect